Speech Acts of The Main Character in Anomalisa Movie Script by Charlie Kaufman - Tri Octavia Agustina; Dahlia D. Moelier; Andi Tenri Abeng (Fakultas Sastra, Universitas Bosowa, 2022)
The research aimed to find out the types of speech acts and the function of speech acts produced by the main character which contained in Anomalisa movie script written by Charlie Kaufman. The researcher used qualitative descriptive and pragmatic approach in analyzing the data. The data were obtained by reading, identifying, classifying the words that contained speech acts in the main character’s utterance in the movie script by applying the Austin and Searle’s theories. The results show that there were three types of speech acts used in Anomalisa movie script, they were (1) Locutionary(2) Illocutionary (3) Perlocutionary, each speech acts have functions, they were (1) Locutionary which consisted of imperative, interrogative and declarative. (2) Illocutionary which consisted of directive, assertive, commissive and expressive. Then, (3) Perlocutionary which consisted of act of laughing, act of asking, act of scaring, act of inviting and act of persuading. The dominant speech act used in the movie script of Anomalisa is Illocutionary.